Hyaluronic acid derivatives or salts thereof, their production method and use

By bonding polyethylene glycol to hyaluronic acid via an ether bond, the derivative addresses biodegradation and mechanical strength issues, offering improved biocompatibility and reduced adverse reactions, suitable for medical cosmetic products.

JP2024546197AActive Publication Date: 2024-12-17JENKEM TECH CO LTD TIANJIN
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024540851
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-01-14
Filing Date
2023-01-09
Publication Date
2024-12-17
Estimated Expiration
2043-01-09

AI Technical Summary

Technical Problem

Conventional hyaluronic acid derivatives, such as sodium hyaluronate, are prone to biodegradation, have low mechanical strength, and residual cross-linking agents can cause immune responses and toxicity when injected into the body, limiting their applications due to insufficient mechanical strength and biocompatibility.

Method used

A hyaluronic acid derivative is produced by bonding polyethylene glycol to hyaluronic acid through an ether bond using a methoxypolyethylene glycol epoxy derivative, forming a composite polymer material that is not cross-linked, maintaining biocompatibility and enhancing resistance to enzymatic degradation.

Benefits of technology

The resulting hyaluronic acid derivative retains moisture and hydration properties while improving mechanical strength, reducing the frequency of injections, enhancing patient comfort, and minimizing adverse reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024546197000001_ABST
    Figure 2024546197000001_ABST
Patent Text Reader

Abstract

The present invention provides a hyaluronic acid derivative or a salt thereof, a method for producing the same and a method for using the same, and a method for producing a matrix metalloproteinase comprising the steps of: The hyaluronic acid is modified with a methoxypolyethylene glycol epoxy derivative as the backbone. The polyethylene glycol derivative of hyaluronic acid is produced. By wrapping the hyaluronic acid skeleton using a linear polymer, it is resistant to enzymatic degradation. Masks glycosidic bonds in the pancreas, prolonging the circulation time of sodium hyaluronate in the body, It exerts a water-retaining effect. In addition, polyethylene glycol and sodium hyaluronate, As a synthetic and natural polymer material, it has excellent biocompatibility and biodegradability. The advantage of combining these materials is that it is possible to make better use of the properties of polymer materials.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the technical field of polymers, in particular to a hyaluronic acid derivative or its salt, and a method for producing the same. Regarding the law and use. [Background technology]

[0002] Hyaluronic acid (HA) is found in the joint fluids of animals and humans, in the eyes, and in the skin. A naturally occurring biological substance found widely in connective tissues such as the vitreous body of the globus, skin, intercellular spaces, and cockscomb. It is a polymeric material and an important component of synovial fluid, vitreous body, skin and cartilage tissue. It has unique physical and chemical properties and a wide range of biological functions. It has biocompatibility, unique viscoelasticity, and excellent moisturizing and water-retaining properties, making it widely used in the beauty industry. Beloved by many beauty enthusiasts, it is now used to reduce wrinkles, improve the appearance of skin and prevent skin aging. It can be injected into the skin of the face to reduce the

[0003] During production and use, hyaluronic acid exists mostly in the form of sodium hyaluronate. Natural sodium hyaluronate is easily biodegradable, has a short retention time in the body, and has low hardness. Its applications are limited due to its insufficient mechanical strength and elasticity. It is common to use a crosslinking agent to gel sodium hyaluronate. A cross-linked modified gel that maintains biocompatibility and significantly improves resistance to enzymatic degradation has been developed. However, it is impossible to completely remove the crosslinker residues using conventional techniques. Most crosslinkers are chemical reagents, and excessive crosslinking can lead to reduced biocompatibility. However, when injected into the human body, it is likely to trigger an immune response, irritate the skin, and even cause cell death. May cause toxicity.

[0004] In the study of non-crosslinked sodium hyaluronate, see Adrian Ranga, et al. Hyaluronic acid id hydrogels formed in situ by transglutaminase-catalyzed reaction[J].Biomacromo lecules, and Kazuteru Moriyama, etc.Hyaluronic acid grafted with poly(ethylene gl ycol) as a novel peptide formulation. Journal of Controlled Release is To bind polyethylene glycol by reacting the carboxyl of sodium salt molecule has been reported to be used.

[0005] LiteratureIrina M.Le-Deygen,etc.Poly(Ethylene Glycol)Interacts with Hyaluronan in Aque ous Media. Biomacromolecules contain hydroxyl and polyamines in the sodium hyaluronate molecule. It is possible to bond polyethylene glycol by utilizing hydrogen bonds between polyethylene glycols. It was reported.

[0006] In the prior art, the amino, carboxy and hydroxyl groups of the sodium hyaluronate molecule are By reacting with polyethylene glycol, polyethylene glycol-based hyaluronic acid with different properties is obtained. However, currently, the sodium hyaluronate molecule is The epoxy was reacted with methoxypolyethylene glycol epoxy derivative to obtain sodium hyaluronate. The thorium molecule was modified with an ether bond to form a polyethylene glycol-based hyaluronan. There is no method to produce sodium phosphate. Summary of the Invention

[0007] The present invention overcomes the drawbacks of the prior art, and in a first aspect of the invention, comprises a structure represented by formula (I): The present invention provides a hyaluronic acid derivative or a salt thereof having the above structure.

[0008] TIFF2024546197000002.tif8271 (where X is -(CR 1 R 2 ) m -, -(CH 2 ) m NH-, -NHCO(CH 2 ) m -, -(CH 2 ) m CONH- and -CO(CH 2 ) m -One or more selected from A combination of several types, m being an integer from 1 to 10; R 1 and R 2 are independently H, alkyl, cycloalkyl, cycloalkylalkyl, Alkenyl, aryl, aralkyl, heterocyclyl, heterocyclylalkyl, -CO R 3 , -C(O)OR 3 , -C(O)NR 3 R 4 , -CH=NR 3 , -CN, -OR 3 , -OC(O)R 3 , -S(O) n -R 3 , -NR 3 R 4 , -NR 3 C(O)R 4 , and Ha Selected from the Rogen n is selected from 0, 1, and 2; R 3 and R 4 are each independently hydrogen, alkyl, cycloalkyl, alkenyl, or a selected from aryl, heterocyclyl, and halogen; k is the degree of polymerization of the polyethylene glycol residue, and k is an integer of 40 to 4600 (e.g., 40, 41, 42, 43, 45, 46, 47, 48, 49, 50, 55, 60, 65 , 70, 75, 80, 85, 90, 95, 100, 105, 110, 111, 112, 1 13, 114, 115, 116, 117, 118, 119, 120, 150, 200, 4 00, 500, 800, 1000, 2000, 3000, 4000, 4500), preferred Preferably, it is an integer of 45 to 4545, more preferably an integer of 75 to 4545, and particularly preferably , an integer between 100 and 4545; t is the degree of polymerization of the hyaluronic acid residue, and t is an integer of 100 to 8000 (for example, 10 0, 105, 110, 115, 120, 125, 130, 135, 140, 145, 15 0, 200, 300, 400, 500, 1000, 2000, 3000, 4000, 50 00, 5500, 6000, 5500, 7000, 7100, 7200, 7300, 74 00), preferably an integer of 120 to 7500, more preferably an integer of 700 to 6000. number, particularly preferably an integer of 1000 to 4000; Preferably, X is -(CR 1 R 2 ) m - and Preferably, m is an integer of 1 to 5, for example, 1, 2, 3, 4, or 5.

[0009] In one embodiment of the present invention, said m=1.

[0010] Preferably, the R1 and R 2 are independently H, C 1 ~C 6 Alkyl, C 3 ~C 6 of Cycloalkyl, -OR 3 , -NR 3 R 4 and halogen.

[0011] Preferably, the R 3 and R 4 are independently hydrogen and C 1 ~C 3 Select from the alkyl will be done.

[0012] In one embodiment of the present invention, the R 1 and R 2 are both H.

[0013] In one preferred embodiment of the present invention, X is -CH 2 -It is.

[0014] The salts include sodium salts, potassium salts, calcium salts, magnesium salts, zinc salts, cobalt salts, and tetrabutylammonium salts, preferably one or more selected from the group consisting of tetrabutylammonium salts and tetrabutylammonium salts. is the sodium salt.

[0015] In one embodiment of the invention, the hyaluronic acid derivative has the following structure: TIFF2024546197000003.tif8073

[0016] In a second aspect of the present invention, A step of weighing hyaluronic acid, mixing the hyaluronic acid with an alkaline solvent, and stirring the mixture ( 1) and Add the methoxypolyethylene glycol epoxy derivative to the solution obtained in step (1). and (2) reacting the The methoxypolyethylene glycol epoxy derivative has the structure of formula (III): The present invention provides a method for producing the hyaluronic acid derivative of formula (II) or a salt thereof. TIFF2024546197000004.tif1555

[0017] Preferably, the alkaline solvent in step (1) is sodium hydride, potassium hydride, One of the following: sodium carbonate, potassium carbonate, sodium bicarbonate, and potassium bicarbonate It is a species or multiple species.

[0018] In one preferred embodiment of the present invention, the alkaline solvent has a mass concentration of 0.25% to 0.8% sodium hydride solution (e.g., 0.25%, 0.35%, 0.5%, 0.8 %), and preferably, the sodium hydride solution has a mass concentration of 0.35% to 0.5%.

[0019] The molecular weight of the sodium hyaluronate is 40,000 to 3.2 million daltons, preferably 50,000 to 5. 3 million daltons, more preferably 280,000 to 2.4 million daltons, particularly preferably 40 The average molecular weight ranges from 10,000 to 1.6 million Daltons.

[0020] The mass ratio of the hyaluronic acid to the alkaline solvent is 1:5 to 30 (specifically, for example, 1 1:5, 1:10, 1:15, 1:20, 1:25 or 1:30), preferably 1:10 It is.

[0021] The model of the polymer units in the hyaluronic acid and methoxypolyethylene glycol epoxy derivative The ratio of the fluorine atom to the fluorine atom is 0.1 to 10:1 (specifically, for example, 0.1:1, 0.2:1, 0.3:1 , 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1 , 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1 , 5.5:1, 6:1, 6.5:1, 7:1, 7.5:1, 8:1, 8.5:1, 9:1 , 9.5:1, 10:1).

[0022] In step (1), the stirring time is 5 to 50 minutes, preferably 10 to 30 minutes. n (e.g., 15min, 16min, 17min, 18min, 19min, 20min n), and more preferably 10 to 20 minutes.

[0023] In step (2), the polyethylene glycol epoxy derivative is a monomethoxypoly ethylene glycol ethylene oxide, and preferably the monomethoxypolyethylene The molecular weight of the glycol ethylene oxide is 2,000 to 200,000, for example, 2,000 , 3000, 4000, 5000, 10000, 20000, 30000, 50000, The number is 100,000.

[0024] In step (2), the reaction includes stirring and then allowing to stand.

[0025] Preferably, in step (2), the reaction time is 10 to 24 hours, preferably 13 to 24 hours. 21 hours, more preferably 17 to 19 hours.

[0026] Preferably, the method for producing a hyaluronic acid derivative or a salt thereof includes a step of purifying the product. and purifying the product by adding an acidic reagent to the reaction mixture in step (2). Adjusting the resulting solution to neutrality and / or adding a precipitant to precipitate the product. and / or adding a washing agent to wash the precipitate.

[0027] The acidic reagent is selected from a dilute hydrochloric acid solution, a dilute sulfuric acid solution, a dilute acetic acid solution, and a dilute hypochlorous acid solution. It is one or more types.

[0028] In one embodiment of the invention, the acidic reagent is a dilute hydrochloric acid solution.

[0029] The precipitating agent is acetonitrile or ethanol.

[0030] In one embodiment of the invention, the precipitating agent is acetonitrile.

[0031] The cleaning agent is ethanol or water.

[0032] In one embodiment of the invention, the cleaning agent is ethanol.

[0033] In one embodiment of the present invention, the method for producing the hyaluronic acid derivative or a salt thereof comprises the steps of: Weigh out the acid, dissolve it in an alkaline solvent, and stir for 10 to 30 minutes until it becomes homogeneous. Add the methoxypolyethylene glycol epoxy derivative and mix the materials evenly. Stir for 10 to 24 hours until the mixture is completely mixed, leave it at room temperature for 15 to 18 hours, and then add an acidic reagent to neutralize the pH of the system. Then, add a precipitant to precipitate the mixture, and vigorously stir the mixture to make the product particles uniform. Centrifuge and leave to stand, remove the supernatant, and continue precipitation with a precipitant for 2 to 5 times to obtain The precipitate was washed with detergent 1 to 3 times, and finally the precipitated product was placed in a vacuum drying oven. Put it in and dry.

[0034] In a third aspect of the present invention, the use of a compound of formula (I) or (II) in the manufacture of a pharmaceutical, medical cosmetic, or cosmetic product is provided. (II) Use of the hyaluronic acid derivative or a salt thereof.

[0035] Preferably, the use comprises the use of said compound of formula (I) or (II) in the manufacture of a medical cosmetic product. The present invention relates to the use of a uronic acid derivative or a salt thereof.

[0036] Preferably, the medical cosmetic product is a soft tissue filler.

[0037] The present invention relates to a soft tissue composition comprising the hyaluronic acid derivative or its salt represented by formula (I) or (II) of the present invention. A woven filler is further provided.

[0038] In the present invention, a polyethylene glycol derivative and hyaluronic acid or a salt thereof are bonded by an ether bond. The reaction product is not a crosslinked gel but a composite polymer material that is soluble in aqueous solution. The produced hyaluronic acid derivative or its salt maintains the water retention and moisturizing properties of hyaluronic acid. Not only does it improve the skin's resistance to hyaluronidase degradation in vivo, it also reduces fine lines on the face and neck. When used in restorations, it reduces the frequency of injections, improves participant comfort, and reduces costs. do. [Brief description of the drawings]

[0039] [Figure 1] 1 shows the relationship between the enzymatic decomposition molecular weight and time for a control sample. [Diagram 2] 1 shows the relationship between enzymatic decomposition molecular weight and time for sample 8. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0040] Unless otherwise defined, all scientific and technical terms used herein are understood to be within the meaning of the present invention. The term "a" has the same meaning as commonly understood by a person skilled in the art. "Alkyl" refers to a straight or branched hydrocarbon chain radical that does not contain unsaturated bonds, In the Ming Dynasty, C 1 ~C 6The alkyl group is methyl, ethyl, n-propyl, isopropyl, 1-6 such as n-butyl, isobutyl, t-butyl, n-pentyl, n-hexyl, etc. Alkyl containing 10 carbon atoms, preferably C 1 ~C 3 Alkyl (methyl, ethyl, n -propyl, isopropyl, etc. "Cycloalkyl" refers to alicyclic hydrocarbons. Representative cycloalkyls contain 1 to 4 single and / or fused rings and 3 to about 18 rings. Contains carbon atoms, and in the present invention, 3 ~C 6 The cycloalkyl in the formula is cyclopropyl, Refers to cycloalkyl containing 3 to 6 carbon atoms, such as cyclopentyl and cyclohexyl. .

[0041] The following clearly and completely describes the technical means in the embodiments of the present invention. It is apparent that the examples are merely some of the embodiments of the present invention, and are not all of the embodiments. Based on the embodiment, all other embodiments obtained by a person skilled in the art without any creative effort. are within the protection scope of the present invention. Example 1

[0042] Weigh out 380 mg of HA (600,000) and dissolve it in 3.8 ml of 0.25% sodium hydride solution. Dissolve the mixture, stir vigorously for 10 to 30 minutes until homogenous, and mix with M-PEG2000-EPOX( TIFF2024546197000005.tif1334, Beijing Keykai Technology Co., Ltd. (same as below) 1g was added and the materials were mixed evenly. The mixture was stirred vigorously until the mixture was completely dissolved, and then left at room temperature for 18 hours. The next day, 1 ml of 0.25N HCl was added. Adjust the pH of the system to about 7, then add 20 ml of acetonitrile to precipitate, and stir vigorously. The product particles were homogenized by stirring, centrifuged, and then the supernatant was removed. The precipitate was precipitated four times with 20 ml of ethanol, and then washed twice with 20 ml of absolute ethanol. The product was dried in a vacuum drying oven to obtain Sample 1 (0.25% NaOH). Multi-angle optical differential detection and nuclear magnetic detection were performed using sampling. Example 2

[0043] Weigh out 570 mg of HA (600,000) and dissolve it in 5.7 ml of 0.35% sodium hydride solution. Dissolve the mixture in water and stir vigorously for 10 to 30 minutes until it becomes homogeneous. Add 1.5 g of the mixture, stir vigorously until the ingredients are uniformly mixed, and leave at room temperature for 18 hours. The next day, 1.5 ml of 0.35N HCl was added to adjust the pH of the system to about 7, and then Add 30 ml of acetonitrile to precipitate, stir vigorously to homogenize the product particles, and then centrifuge. The mixture was separated and allowed to stand, and the supernatant was removed. The mixture was precipitated four times with 30 ml of acetonitrile. The product was then washed twice with 30 ml of absolute ethanol and dried in a vacuum oven. Sample 2 (0.35% NaOH) was obtained. And nuclear magnetic detection was performed. Example 3

[0044] Weigh out 380 mg of HA (600,000) and dissolve it in 3.8 ml of 0.5% sodium hydride solution. Stir vigorously for 10-30 minutes until homogenous, then add M-PEG2000-EPOX 1 g was added, and the mixture was stirred vigorously until it was uniformly mixed, and then the mixture was left at room temperature for 18 hours. On the day of the test, 1 ml of 0.5N HCl was added to adjust the pH of the system to about 7, and then acetonitrile was added. Add 20 ml of ethanol to precipitate, stir vigorously to homogenize the product particles, centrifuge, and let stand. The supernatant was removed. The precipitation was continued four times with 20 ml of acetonitrile, and then with anhydrous Wash twice with 20 ml of ethanol, then place the product in a vacuum drying oven to dry, and then sample 3 (0.5% NaOH) was obtained. Sampling was performed using multi-angle optical differential detection and nuclear magnetic detection. went. Example 4

[0045] Weigh out 380 mg of HA (600,000) and dissolve it in 3.8 ml of 0.8% sodium hydride solution. Stir vigorously for 10-30 minutes until homogenous, then add M-PEG2000-EPOX 1 g was added, and the mixture was stirred vigorously until it was uniformly mixed, and then the mixture was left at room temperature for 18 hours. On the day of the test, 1 ml of 0.8N HCl was added to adjust the pH of the system to about 7, and then acetonitrile was added. Add 20 ml of ethanol to precipitate, stir vigorously to homogenize the product particles, centrifuge, and let stand. The supernatant was removed. The precipitation was continued four times with 20 ml of acetonitrile, and then with anhydrous Wash twice with 20 ml of ethanol, then place the product in a vacuum drying oven to dry, and then sample 4 (0.8% NaOH) was obtained. Sampling was performed using multi-angle optical differential detection and nuclear magnetic detection. went. Example 5

[0046] Weigh out 190 mg of HA (600,000) and dissolve it in 5.7 ml of 0.35% sodium hydride solution. Dissolve the mixture in water and stir vigorously for 10 to 30 minutes until it becomes homogeneous. Add 500 mg, stir vigorously until the ingredients are uniformly mixed, and leave at room temperature for 18 hours. The next day, 1 ml of 0.35N HCl was added to adjust the pH of the system to about 7. Add 10 ml of acetonitrile to precipitate, vigorously stir to homogenize the product particles, and then centrifuge. The mixture was allowed to stand and the supernatant was removed. The precipitation was continued four times with 10 ml of acetonitrile. The product was then washed twice with 10 ml of absolute ethanol and dried in a vacuum oven. Sample 5 (0.35% NaOH) was obtained. Sampling was performed using multi-angle optical differential detection and Nuclear magnetic detection was performed. Example 6

[0047] Weigh out 760 mg of HA (600,000) and dissolve it in 7.6 ml of 0.35% sodium hydride solution. Dissolve the mixture in water and stir vigorously for 10 to 30 minutes until it becomes homogeneous. 2 g was added, and the mixture was stirred vigorously until the materials were uniformly mixed, and then allowed to stand at room temperature for 15 hours. The next day, add 2 ml of 0.35N HCl to adjust the pH of the system to about 7, then add acetonitrile. Add 40 ml of trityl to precipitate, stir vigorously to homogenize the product particles, and then centrifuge to separate. The mixture was allowed to stand, and the supernatant was removed. The mixture was precipitated four times using 40 ml of acetonitrile. Wash twice with 40 ml of absolute ethanol, then place the product in a vacuum drying oven to dry and sanitize. Pool 6 (0.35% NaOH) was obtained. Samples were then used for multi-angle optical differential detection and nuclear magnetic resonance (NMR) analysis. Detection was carried out. Example 7

[0048] Weigh out 760 mg of HA (600,000) and dissolve it in 7.6 ml of 0.35% sodium hydride solution. Dissolve the mixture in water and stir vigorously for 10 to 30 minutes until it becomes homogeneous. 2 g was added, and the mixture was stirred vigorously until the materials were uniformly mixed, and then allowed to stand at room temperature for 21 hours. The next day, add 2 ml of 0.35N HCl to adjust the pH of the system to about 7, then add acetonitrile. Add 40 ml of trityl to precipitate, stir vigorously to homogenize the product particles, and then centrifuge to separate. The mixture was allowed to stand, and the supernatant was removed. The mixture was precipitated four times using 40 ml of acetonitrile. Wash twice with 40 ml of absolute ethanol, then place the product in a vacuum drying oven to dry and sanitize. Pool 6 (0.35% NaOH) was obtained. Samples were then used for multi-angle optical differential detection and nuclear magnetic resonance (NMR) analysis. Detection was carried out. Example 8

[0049] Weigh out 570 mg of HA (600,000) and dissolve it in 5.7 ml of 0.35% sodium hydride solution. Dissolve the mixture in water and stir vigorously for 10 to 30 minutes until it becomes homogeneous. Add 2750 mg of ethanol, stir vigorously until the material is uniformly mixed, and leave at room temperature for 18 hours. The next day, 2 ml of 0.35N HCl was added to adjust the pH of the system to about 7, and then Add 30 ml of acetonitrile to precipitate, vigorously stir to homogenize the product particles, and centrifuge. The mixture was separated and allowed to stand, and the supernatant was removed. The mixture was precipitated four times with 30 ml of acetonitrile. The product was then washed twice with 30 ml of absolute ethanol and dried in a vacuum oven. Sample 8 (0.35% NaOH) was obtained. And nuclear magnetic detection was performed. Example 9

[0050] Weigh out 570 mg of HA (600,000) and dissolve it in 5.7 ml of 0.35% sodium hydride solution. Dissolve the mixture in water and stir vigorously for 10 to 30 minutes until it becomes homogeneous. Add 1875 mg of ethanol, stir vigorously until the material is uniformly mixed, and leave at room temperature for 18 hours. The next day, 2 ml of 0.35N HCl was added to adjust the pH of the system to about 7, and then Add 30 ml of acetonitrile to precipitate, vigorously stir to homogenize the product particles, and centrifuge. The mixture was separated and allowed to stand, and the supernatant was removed. The mixture was precipitated four times with 30 ml of acetonitrile. The product was then washed twice with 30 ml of absolute ethanol and dried in a vacuum oven. Sample 9 (0.35% NaOH) was obtained. And nuclear magnetic detection was performed. Example 10

[0051] Weigh out 570 mg of HA (600,000) and dissolve it in 5.7 ml of 0.35% sodium hydride solution. Dissolve the mixture in water and stir vigorously for 10 to 30 minutes until it becomes homogeneous. Add 7500 mg of the mixture, stir vigorously until the ingredients are uniformly mixed, and leave at room temperature for 18 hours. The next day, 2 ml of 0.35N HCl was added to adjust the pH of the system to about 7, and then Add 30 ml of acetonitrile to precipitate, vigorously stir to homogenize the product particles, and centrifuge. The mixture was separated and allowed to stand, and the supernatant was removed. The mixture was precipitated four times with 30 ml of acetonitrile. The product was then washed twice with 30 ml of absolute ethanol and dried in a vacuum oven. Sample 10 (0.35% NaOH) was obtained. And nuclear magnetic detection was performed. Example 11

[0052] Weigh out 570 mg of HA (600,000) and dissolve it in 5.7 ml of 0.35% sodium hydride solution. The mixture was dissolved, stirred vigorously for 10 to 30 minutes until it became homogeneous, and then left to stand at room temperature for 18 hours. Add 2 ml of 0.35N HCl to adjust the pH of the system to about 7, then add acetonitrile. Add 30 ml of the mixture to precipitate, stir vigorously to homogenize the product particles, centrifuge and let stand. The supernatant was removed. The precipitation was continued four times with 30 ml of acetonitrile and then with anhydrous ethanol. The product was then washed twice with 30 ml of ethanol and dried in a vacuum drying oven. Sample 1 1 (0.35% NaOH) was obtained. Sampling was performed using multi-angle optical differential detection and nuclear magnetic detection. The molecular weight was 6.366 × 10 5 Da, and sample 11 is To calculate the number of polyethylene glycols attached onto the sodium hyaluronate backbone was used as a comparison sample. Example 12

[0053] The molecular weight information obtained by performing multi-angle optical differential detection on the products in Examples 1 to 4 is As shown in Table 1.

[0054] [Table 1]

[0055] As can be seen from the molecular weight data in Table 1, the alkali concentration of the reaction solution can be either too low or too high. If the concentration of the alkaline solution is too low, the reactivity of the raw material will not be high, and the alkaline solution will If the liquid concentration is too high, the sodium hyaluronate may be decomposed by alkali. There are more.

[0056] Molecular weights obtained by multi-angle optical differential detection of the products in Examples 2 and 5 The information is shown in Table 2.

[0057] [Table 2]

[0058] As can be seen from the molecular weight data in Table 2, too much solvent makes the system too dilute and the raw material The alkaline hydrolysis of sodium hyaluronate is accelerated.

[0059] The products in Examples 2, 6, and 7 were subjected to multi-angle optical differential detection. The molecular weight information obtained is shown in Table 3.

[0060] [Table 3]

[0061] As can be seen from the molecular weight data in Table 3, reaction time is also a limiting factor in product performance. If the reaction time is too long, there is a high risk of the raw material sodium hyaluronate deteriorating.

[0062] Multi-angle optical differential detection was performed on the products in Examples 8, 9, and 10. The molecular weight information obtained is shown in Table 4.

[0063] [Table 4]

[0064] As can be seen from the molecular weight data in Table 4, HA and methoxypolyethylene glycol epoxy The feed ratio of the derivatives also has a certain effect on the performance of the product. Example 13

[0065] Taking Sample 2 and Sample 11 as examples, The method for calculating the ratio of the number of sodium hyaluronate disaccharides to the number of PEG in the product is shown below. (The molecular weight of one disaccharide unit is 380.)

[0066] The average number of disaccharide units in sample 11 is 6.366×105 / 380=1675.

[0067] The number of PEG2000 in sample 2 is (12.02-6.366)105 / 20 00=283.

[0068] The ratio of the number of disaccharides to the number of PEG2000 in sample 2 is 1675 / 283=6:1. .

[0069] In vitro enzymatic hydrolysis experiments

[0070] Steps of the experimental procedure for enzymatic hydrolysis For example, take sample 8. Weigh out 3.4 mg of sample 8 and add 242 μl of sterile water for injection. The mixture was then vortexed for 20 min and injected with 10 U / ml hyaluronidase. Add 242 μl of sterile aqueous solution for 10 min, mix the sample evenly, and place in a constant temperature water bath at 37°C. Sampling was performed every hour to test the change in molecular weight by multi-angle optical differential detection method. did.

[0071] The sample information for testing the enzymatic hydrolysis experiment is as follows:

[0072] Control sample: HA 1.2 million Da. The relationship between enzymatic decomposition molecular weight and time is shown in Figure 1.

[0073] Sample 2: The ratio of the number of HA disaccharides to the number of PEG2000 is 6:1.

[0074] Sample 12: The ratio of the number of HA disaccharides to the number of PEG2000 is 17:1.

[0075] Sample 8: The ratio of the number of HA disaccharides to the number of PEG5000 was 13:1, and the enzyme-degraded molecules The dose-time relationship diagram is shown in FIG.

[0076] Sample 9: The ratio of the number of HA disaccharides to the number of PEG5000 is 22:1.

[0077] Sample 13: The ratio of the number of HA disaccharides to the number of PEG5000 is 42:1.

[0078] Enzymatic degradation data of PEG5000-HA sample

[0079] [Table 5]

[0080] [Table 6] Enzymatic degradation data of PEG2000-HA sample TIFF2024546197000011.tif50152

[0081] As can be seen from the data in Tables 5 and 6, when the molecular weight of PEG is 5000, HA and PEG When the ratio of PEG to HA was between 13:1 and 42:1, PEG did not affect the resistance of HA to enzymatic degradation. The larger the ratio, the more pronounced the effect. When the molecular weight of PEG is 2000, PEG is It has a significant effect on the resistance of HA to enzymatic degradation.

Claims

1. A hyaluronic acid derivative having a structure represented by formula (I) or a salt thereof. (wherein X is -(CR 1 R 2 ) m -, -(CH 2 ) m NH-, -NHCO(CH 2 ) m -, -(CH 2 ) m CONH- and -CO(CH 2 ) m -One or more selected from A combination of several types, m is an integer from 1 to 10, R 1 and R 2 are independently H, alkyl, cycloalkyl, cycloalkylalkyl, Alkenyl, aryl, aralkyl, heterocyclyl, heterocyclylalkyl, -CO R 3 、-C(O)OR 3 、-C(O)NR 3 R 4 、-CH=NR 3 、-CN、-OR 3 、 -OC(O)R 3 , -S(O) n -R 3 , -NR 3 R 4 , -NR 3 C(O)R 4 , and Ha Selected from the Rogen n is selected from 0, 1, and 2; R 3 and R 4 are each independently hydrogen, alkyl, cycloalkyl, alkenyl, or a selected from aryl, heterocyclyl, and halogen; k is the degree of polymerization of the polyethylene glycol residue, and k is an integer from 40 to 4600. 、 t is the degree of polymerization of the hyaluronic acid residue, and t is an integer from 100 to 8000.

2. The k is an integer of 45 to 4545, preferably an integer of 75 to 4545, more preferably , an integer from 100 to 4545; The t is an integer of 120 to 7500, preferably an integer of 700 to 6000, more preferably The hyaluronic acid according to claim 1, characterized in that the hyaluronic acid is an integer between 1,000 and 4,000. Acid derivatives or their salts.

3. The X is -(CR 1 R 2 ) m -, wherein m is an integer of 1 to 5, preferably 1. The hyaluronic acid derivative or its salt according to claim 1,

4. The R 1 and R 2 are independently H, C 1 ~C 6 Alkyl, C 3 ~C 6 Cycloalkane Ru, -OR 3 , -NR 3 R 4 and halogen, 3 and R 4 is independent Hydrogen and C 1 ~C 3 2. The method according to claim 1, wherein the alkyl group is selected from the group consisting of A hyaluronic acid derivative or a salt thereof.

5. The R 1 and R 2 The hyaluronic acid according to claim 1, characterized in that Acid derivatives or their salts.

6. The salts include sodium salts, potassium salts, calcium salts, magnesium salts, zinc salts, cobalt salts, and tetrabutylammonium salts, preferably one or more selected from the group consisting of tetrabutylammonium salts and tetrabutylammonium salts. is a sodium salt having the structure of formula (II). Hyaluronic acid derivatives or salts thereof.

7. A step of weighing hyaluronic acid, mixing hyaluronic acid with an alkaline solvent, and stirring the mixture ( 1) and Add the methoxypolyethylene glycol epoxy derivative to the solution obtained in step (1). and (2) reacting the The methoxypolyethylene glycol epoxy derivative has the structure of formula (III): A method for producing the hyaluronic acid derivative or its salt according to claim 1.

8. further comprising purifying the product; The step of purifying the product comprises: Adding an acidic reagent to adjust the solution obtained in step (2) to neutral; and / or adding a precipitating agent to precipitate the product, and / or adding a washing agent to wash the precipitate. The method of claim 7, further comprising the step of: Manufacturing method.

9. The mass ratio of the hyaluronic acid to the alkaline solvent is 1:5 to 30, preferably 8. The method according to claim 7, wherein the weight ratio of the uronic acid to the alkaline solvent is 1:

10. A method for producing the above-mentioned hyaluronic acid derivative or a salt thereof.

10. The model of the polymer units in the hyaluronic acid and methoxypolyethylene glycol epoxy derivative 8. The hyaluronic acid derivative according to claim 7, wherein the ratio of the hyaluronic acid to the hyaluronic acid is 0.1 to 10:

1. Or a method for producing a salt thereof.

11. In step (2), the reaction time is 10 to 24 hours, preferably 13 to 21 hours, more preferably The hyaluronic acid derivative according to claim 7, characterized in that the period is preferably 17 to 19 hours. A method for producing the compound or a salt thereof.

12. The hyaluronic acid derivative according to claim 1 in the manufacture of pharmaceutical, medical cosmetic and cosmetic products. Use of the body or a salt thereof, Preferably, the use comprises the use of the hyaluronic acid derivative or The use of that salt, More preferably, the medical cosmetic product is a soft tissue filler.

Citation Information

Patent Citations

  • Multi-glycol epoxy derivative cross-linked sodium hyaluronate gel used for injection and preparation method thereof

    CN107880282A

  • Hydroxyalkylated hyaluronic acid

    JP2006312725A

  • Tunably crosslinked hyaluronic acid compositions

    JP2014194018A

  • Modified hyaluronic acid, its production method and its uses

    JP2019509385A

  • Modified hyaluronic acid and / or salt thereof, method for producing same and cosmetic comprising same

    WO2011102462A1